Single-crystal X-ray diffraction study, NMR and electrochemical analysis of a copper(i) 5, 11, 17, 23-tetra-tert-butyl-25, 26, 27, 28-tetrakis-[(6-methyl-2, 2′-bipyridyl-6-yl)methoxy]calix[4]arene complex: an original M4L2 "hand-to-hand" system. (7th August 2019) - Regnouf-de-Vains, J.-B.; Malaman, B.; Bouguet-Bonnet, S.; Poinsignon, Sophie; Leclerc, Sébastien; Beley, M.
Abstract : An original M4 L2 "hand-to-hand" copper(i )/tetra-bipyridyl-calix[4]arene complex was obtained and characterized in the solid state by X-ray diffraction. It changes in MeCN solution to its M2 L analogue. Abstract : Attempts to prepare a supramolecular M4 L2 box involving two tetra-bipyridyl calix[4]arene units and four copper(i ) cations afforded, in fact, complex2 for which, in the solid state, X-ray diffraction analysis showed that the stoichiometry is indeed M4 L2, with the two calixarene subunits associated in a "hand-to-hand" mode by complexation via two adjacent bipyridine units to two copper(i ) cations, and each group of two residual, adjacent, bipyridine arms is complexed to one copper(i ) centre. Mass spectrometry, UV spectroscopy and preliminary 1 H-NMR analysis are in preliminary accordance with a monocalixarenic right/left handed M2 L structure. Nevertheless, some particularities of the NMR spectrum related to Ar-CH2 -Ar and O-CH2 bpy resonance signals, the possible generation of the M2 L species during the mass spectrometry experiment and the lack of sensitivity of the UV-visible titration caused us to proceed to deeper investigations, looking for other associations, notably the M4 L2 "hand-to-hand" systems. This involved 1D and 2D-NMR spectroscopies, among them 1 H– 15 N HMBC, for the reconstruction of the molecule, but also the measurement of self-diffusion coefficients by NMR and electrochemistry. The 2D-NMR analysis and NMR self-diffusion evaluation were in accordance with the M2 L structure, but the electrochemical self-diffusion experiment indicated a M4 L2 structure.